TGF-β Inhibitors for Therapeutic Management of Kidney Fibrosis - Cheol Ho Park; Tae-Hyun Yoo (MDPI AG, 2022)
Kidney fibrosis is a common pathophysiological mechanism of chronic kidney disease (CKD) progression caused by several underlying kidney diseases. Among various contributors to kidney fibrosis, transforming growth factor-β1 (TGF-β1) is the major factor driving fibrosis. TGF-β1 exerts its profibrotic attributes via the activation of canonical and non-canonical signaling pathways, which induce proliferation and activation of myofibroblasts and subsequent accumulation of extracellular matrix. Over the past few decades, studies have determined the TGF-β1 signaling pathway inhibitors and evaluated whether they could ameliorate the progression of CKD by hindering kidney fibrosis. However, therapeutic strategies that block TGF-β1 signaling have usually demonstrated unsatisfactory results. Herein, we discuss the therapeutic concepts of the TGF-β1 signaling pathway and its inhibitors and review the current state of the art regarding regarding TGF-β1 inhibitors in CKD management.